High-resolution 3-dimensional photonic scan-derived equations improve body surface area prediction in diverse populations - Ashby-Thompson, Maxine (Obesity (Silver Spring), 2020)
OBJECTIVE: Equations for predicting Body Surface Area (BSA) produce flawed estimates, especially for individuals with obesity. We aimed to compare BSA measured by a 3-dimensional photonic scanner (BSA(3DPS)) to BSA predicted by six commonly cited prediction equations, and to develop new prediction equations if warranted. METHODS: We validated the 3DPS against manual measurements by breadth caliper for body thicknesses measured at three anatomical sites on a mannequin. BSA was derived from 3DPS whole body scans of 67 males and 201 females, ages 18-83; BMIs 17.8-77.8 kg/m(2), and varied race/ethnicities. RESULTS: Width and depth measurements by 3DPS and caliper were within 1%, except for hip, error 1.8%. BSA(3DPS) differed from BSA predicted by each equation (p<0.05), except for males by DuBois (p=0.60), Tikuisis (p=0.27) and Yu (p=0.45), and for females by Tikuisis (p=0.70). The combined and sex-specific equations obtained by regressing ln(BSA) on ln(W) and ln(H), are (W=weight kg; H=height m, R(2) and SEE correspond to ln(BSA)): Combined: BSA(3DPS)=0.03216 x W(0.4904) x H(0.3769), R(2)=0.982, SEE=0.021; Males: BSA(3DPS)=0.01624 x W(0.4725) x H(0.5231); Females: BSA(3DPS)=0.01522 x W(0.4921) x H(0.5231), R(2)=0.986, SEE=0.019. CONCLUSION: New height and weight BSA equations improve BSA estimations in BMI ≥ 40 kg/m(2), African Americans, Hispanic Americans and Asian Americans.